Open surgical versus minimal invasive necrosectomy of the pancreas: a retrospective multicenter analysis of the German Pancreatitis Study Group - Rasch, Sebastian; Rückert, Felix; Post, Stefan (PLOS ONE, 2016)
Background: Necrotising pancreatitis, and particularly infected necrosis, are still associated with high morbidity and mortality. Since 2011, a step-up approach with lower morbidity rates compared to initial open necrosectomy has been established. However, mortality and complication rates of this complex treatment are hardly studied thereafter. Methods: The German Pancreatitis Study Group performed a multicenter, retrospective study including 220 patients with necrotising pancreatitis requiring intervention, treated at 10 hospitals in Germany between January 2008 and June 2014. Data were analysed for the primary endpoints "severe complications" and "mortality" as well as secondary endpoints including "length of hospital stay", "follow up", and predisposing or prognostic factors. Results: Of all patients 13.6% were treated primarily with surgery and 86.4% underwent a step-up approach. More men (71.8%) required intervention for necrotising pancreatitis. The most frequent etiology was biliary (41.4%) followed by alcohol (29.1%). Compared to open necrosectomy, the step-up approach was associated with a lower number of severe complications (primary composite endpoint including sepsis, persistent multiorgan dysfunction syndrome (MODS) and erosion bleeding: 44.7% vs. 73.3%), lower mortality (10.5% vs. 33.3%) and lower rates of diabetes mellitus type 3c (4.7% vs. 33.3%). Low hematocrit and low blood urea nitrogen at admission as well as a history of acute pancreatitis were prognostic for less complications in necrotising pancreatitis. A combination of drainage with endoscopic necrosectomy resulted in the lowest rate of severe complications. Conclusion: A step-up approach starting with minimal invasive drainage techniques and endoscopic necrosectomy results in a significant reduction of morbidity and mortality in necrotising pancreatitis compared to a primarily surgical intervention.